(untitled) - Yuan, Gao (New York, 1991)
Elaborated, enriched, and perfected by generations of soldiers, politicians, merchants, philosophers, and poets during five millennia of wars, coups, court intrigue, and economic turmoil, the 36 Stratagems are a compendium of history, legend, and military lore.
Keywords: Strategic planning,Lập kế hoạch chiến lược